THE CURRENT STATE OF ECOLOGY AND THE ENVIRONMENT AND THE URGENCY OF ITS PROTECTION (International Congress on Economics, Management and Business Studies, 2026)
This article examines the current state of ecology and the environment, as well as the impact of human activities on nature and the growing importance of environmental protection. The problems of atmospheric, water, and soil pollution, the reduction of biodiversity, and the consequences of global climate change are analyzed. The study also highlights the necessity of maintaining ecological balance, rational use of natural resources, and the implementation of environmentally friendly technologies. Furthermore, the importance of developing environmental awareness and ecological culture among society is emphasized. Environmental protection is considered an essential factor for sustainable development and the well-being of future generations.
Keywords: Ecology, environment, environmental problems, air pollution, water resources, soil degradation, biodiversity, global climate change, ecological balance, ecological culture, natural resources, sustainable development.